Mechanisms of hot corrosion of pure nickel at 700°C: Influence of testing conditions. (15th August 2018) - Grégoire, Benjamin; Montero, Xabier; Galetz, Mathias C.; Bonnet, Gilles; Pedraza, Fernando
Highlights: Mechanisms of hot corrosion governed by both p O 2 and p S O 3 . Inward transport of SO2 /SO3 demonstrated to rule the oxidation-sulphidation of pure nickel. The Na2 SO4 deposit decreases the p O 2 and the p S O 3 at the scale surface. A sufficient p S O 3 is required to stabilize Na2 SO4-NiSO4 liquid solutions and simulate Type-II hot corrosion conditions. The role of capillarity effects is elucidated. Abstract: The hot corrosion behaviour of pure nickel was investigated at 700 °C to highlight the influence of testing conditions (composition of the atmosphere and presence or not of a Na2 SO4 deposit) on the mechanisms of hot corrosion. The influence of SO2 /SO3 inward transport through the porous NiO growing scales was studied by exposing nickel in synthetic air and in synthetic air + 0.5% SO2 /SO3 without Na2 SO4 . The addition of Na2 SO4 decreased the p O 2 and the p S O 3 at the sample surface, which promoted the formation of Ni-S liquid solution at the metal/scale interface. A sufficient p S O 3 was required to stabilize liquid Na2 SO4 -NiSO4 solutions and simulate Type-II hot corrosion conditions.